A MULTI-STATE MARKOV MODEL FOR PROJECTING HEALTH CARE SPENDING - Blanco-Encomienda, Francisco Javier (European Scientific Journal, ESJ, 2013)
Demographic developments have always been central to economic growth and welfare. One of the observed trends has been that people live longer and they also remain healthy for longer. Besides this change, regarding the population structure the birth rates have declined, causing the so-called ‘progressive aging of the population’. Since the aging process is important in the field of social protection, spending on health and long-term care for dependent older people is a first-order policy issue. In this respect, considerable attention has focused on projecting these health care expenditures; emphasis has been given to estimating the number of dependent older people so that government can direct resources and services efficiently and effectively. These projections can be obtained by a multi-state Markov model, which is presented in this paper. Projections of dependency amongst the elderly provides the basis for assessing the future cost of associated health care and the necessary services in order to guarantee that requirements for the dependent population are suitably covered.